Nigeria Agriculture Public Expenditure Review - Mogues, Tewodaj; Morris, Michael L.; Freinkman, Lev; Adubi, Abimbola; Ehui, Simeon; Nwoko, Chinedum; Taiwo, Olufemi; Nege, Caroline; Okonji, Patrick; Chete, Louis (International Food Policy Research Institute, 2008)
Most of Nigeria's poor reside in rural areas and gain their livelihood from agricultural work. If the government's poverty reduction goals are to be achieved, Nigeria will need an adequate level of strategically targeted investments in agriculture to upgrade rural infrastructure, boost productivity, and increase competitiveness. Before effective investment programs can be designed and implemented, however, it is important to have a clear understanding of the current pattern of public spending on agriculture. The Nigeria Agriculture Public Expenditure Review (NAGPER), a collaborative study carried out by a research team from the International Food Policy Research Institute (IFPRI) and the World Bank, assesses the quantity and quality of public spending in agriculture and evaluates its degree of alignment with government policy goals. This brief summarizes NAGPER findings and key recommendations. --Authors' Abstract